Kinetics of small molecule adsorption studied using precision ellipsometry. (8th May 2019) - Yakovlev, Nikolai L.; Quek, Hou Chin; Dąbrowski, Karol M.; Birch, William R.
Abstract : On the basis of a miniature polarisation modulator, a precision ellipsometry system has been made, enabling real‐time measurement of subnanometre thin layers on reflecting substrates. This system monitored the kinetics of adsorption and desorption of propanol, or ethanol, or methanol on oxidised Si substrates. While adsorption of propanol and ethanol increased the thickness, adsorption of methanol showed surprising kinetics: the thickness first increased, then decreased. To explain this, a model of substitutional (or competitive) adsorption has been used, where the target molecule is adsorbed only when it substitutes another one leaving an adsorption site. The model fits the experimental data quantitatively and can predict processes involving several components on solid surfaces. Precision ellipsometry demonstrated its high analytical potential in investigation of surfaces at molecular level.